The interaction between gut microbiota and hibernation in mammals - Gao, Peng; Shen, Wenjing; Bo, Tingbei (Frontiers in Microbiology, 2024)
Hibernation, an evolved survival trait among animals, enables them to endure frigid temperatures and food scarcity during the winter months, and it is a widespread phenomenon observed in mammals. The gut microbiota, a crucial component of animal nutrition and health, exhibits particularly dynamic interactions in hibernating mammals. This manuscript comprehensively evaluates the impacts of fasting, hypothermia, and hypometabolism on the gut microbiota of hibernating mammals. It suggests that alterations in the gut microbiota may contribute significantly to the maintenance of energy metabolism and intestinal immune function during hibernation, mediated by their metabolites. By delving into these intricacies, we can gain a deeper understanding of how hibernating mammals adapt to their environments and the consequences of dietary modifications on the symbiotic relationship between the gut microbiota and the host. Additionally, this knowledge can inform our comprehension of the protective mechanisms underlying long-term fasting in non-hibernating species, including humans, providing valuable insights into nutritional strategies and health maintenance.